2004
DOI: 10.1161/01.cir.0000138932.17956.f1
|View full text |Cite
|
Sign up to set email alerts
|

Prior Statin Therapy Is Associated With a Decreased Rate of Severe Sepsis

Abstract: Background-Statins have anti-inflammatory properties that are independent of their lipid-lowering abilities. We hypothesized that statin therapy before the onset of an acute bacterial infection may have a protective effect against severe sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
270
3
16

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 366 publications
(311 citation statements)
references
References 36 publications
19
270
3
16
Order By: Relevance
“…In a Klebsiella pneumoniae mouse model of pneumonia, lovastatin delayed bacterial clearance and enhanced dissemination (2). In contrast, statins have consistently improved survival in animal and human bacterial sepsis (16,22,83), implying that the beneficial effects of statins may outweigh their potential deleterious effects.…”
Section: Discussionmentioning
confidence: 99%
“…In a Klebsiella pneumoniae mouse model of pneumonia, lovastatin delayed bacterial clearance and enhanced dissemination (2). In contrast, statins have consistently improved survival in animal and human bacterial sepsis (16,22,83), implying that the beneficial effects of statins may outweigh their potential deleterious effects.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate analysis further revealed that only statin use was associated with a decreased mortality rate (132). In a prospective observational cohort study of 361 patients with bacterial infection, statin use was independently associated with a significantly lower rate of severe sepsis (P ϭ 0.001), in addition to a lower relative risk of death (0.43) (133). The results of the latter 2 studies are not yet conclusive; a randomized controlled trial of statin use in sepsis may be warranted.…”
Section: Abeles and Pillingermentioning
confidence: 98%
“…On the other hand, there are evidences [21][22][23][24] and controversies [25][26][27][28][29] that require a better definition that statins, independent of their primary action, help reduce mortality in the treatment of sepsis 21,25,30 , supposedly for inhibiting the synthesis of products of the cholesterol metabolic pathway just before mevalonate is produced, preventing the production of substances such as isoprenoids and geranylgeranyl pyrophosphate 31 . In addition, they modify the intercellular interaction and the chemotaxis of the immune system; have antioxidant properties, although reducing the levels of ubiquinone (CoQ10), an endogenous oxidant 32 ; act against apoptosis; inhibit the action of certain genes, changing the cellular activity; and participate, in other mechanisms, of the inflammatory response 30 , facts that intensify their capability to control the systemic inflammatory response syndrome and protect cardiac patients from complications of noncardiac surgeries [33][34][35] or in similar situations triggered by the infection [22][23][24]36,37 .…”
Section: Sepsismentioning
confidence: 99%
“…However, most studies testing the effect of statins in the treatment of severe diseases present methodological limitation and are retrospective studies 30 . Almog et al 21 , in a prospective study with the participation of several researchers, consecutively enrolled 361 patients admitted with presumed or documented acute bacterial infection. These patients presented high rates of severe sepsis and transference to the intensive care unit.…”
Section: Sepsismentioning
confidence: 99%